Prevalance and Intensity of Helminthiasis in Gastrointestinal Tractus of Goat At Kwanyar Sub-District, Bangkalan District - Alivia Fairuz Ilmi; Sarmanu Sarmanu; Agus Wijaya (Journal of Parasite Science (JoPS), 2020)
This study aims to determine the prevalence and intensity of helminthiasis in gastrointestinal tract of goat at Kwanyar Sub-District, Bangkalan District. The study was conducted in August-October 2018 with 100 samples of stool examination in the laboratory of Helmintology, Division of Veterinary Parasitology, Faculty of Veterinary Medicine, Universitas Airlangga. The results were found various worm eggs such as Oesophagustomum sp., Strongyloides sp., Haemonchus sp., Trichuris sp., and Chabertia sp. Moreover, the prevalence of gastrointestinal helminthiasis was recorded at 100%. In addition, the calculation of worm eggs per gram fecal sample was obtained the number of infecting eggs ranges from 0-500 and the categorized as mild degree of infection. The results of statistical analysis using Chi-Square test was showed no significant differences in the intensity of infection in male and female goats (p>0.05). However, there was significant differences in the intensity of infection in goat between 0-12 months age and above 12 months age (p<0.05).